1983
DOI: 10.1111/j.1471-4159.1983.tb08023.x
|View full text |Cite
|
Sign up to set email alerts
|

Suriclone: A New Cyclopyrrolone Derivative Recognizing Receptors Labeled by Benzodiazepines in Rat Hippocampus and Cerebellum

Abstract: Suriclone (RP 31,264), like zopiclone (RP 27,267), belongs to the family of cyclopyrrolones and is chemically entirely different from the benzodiazepines (BZDs). However, it possesses a pharmacological profile close to that of the BZDs and proved to be useful in therapeutics as an anxiolytic agent. In the present paper it is shown that suriclone possesses a high affinity for flunitrazepam binding sites and that tritiated suriclone binds specifically with high affinity in rat hippocampus (KD = 0.44 +/- 0.03 nM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
2

Year Published

1984
1984
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(19 citation statements)
references
References 23 publications
2
15
0
2
Order By: Relevance
“…This may be the reason why suriclone did not generalize completely to the zopiclone stimuli. Zopiclone binds to benzo diazepine receptors, and its affinity is com parable to those of diazepam and nitrazepam (8,19). In the present studies, diazepam, nitrazepam and alprazolam were also general ized to the zopiclone stimulus.…”
Section: Discussionsupporting
confidence: 51%
“…This may be the reason why suriclone did not generalize completely to the zopiclone stimuli. Zopiclone binds to benzo diazepine receptors, and its affinity is com parable to those of diazepam and nitrazepam (8,19). In the present studies, diazepam, nitrazepam and alprazolam were also general ized to the zopiclone stimulus.…”
Section: Discussionsupporting
confidence: 51%
“…By contrast, DN 2327 was more potent and longer lasting than diazepam in its ability to protect against the effects of pentylenetetrazol. CGS9896 (17) and suriclone (18) have been reported to possess good separation ratios between their anxiolytic and muscle-relaxant actions, and it has also been shown that these two com pounds have a more potent protective effect against pentylenetetrazol-induced convulsion than against bicuculline or picrotoxin induced convulsion. In the neurochemical study, DN-2327 showed a more potent af finity for benzodiazepine receptors than did diazepam.…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of psy choactive drugs has, therefore, been investigated includ ing classical benzodiazepines and non-benzodiazepine compounds which displace benzodiazepines from their binding sites on brain membranes. Of these, suriclone (a benzodiazepine-like cyclopyrrolone) [11] has anxiolytic activity [12], but has the full profile of activities of clas sical benzodiazepines [13], whilst CL 218872 [14,25] and premazepam [15] have anxiolytic, but less musclerelaxant and/or sedative properties. In addition, the an xiolytics buspirone [16] and sodium valproate (which is active in other models of anxiety) [17][18][19] do not dis place central benzodiazepine binding and have also been tested.…”
Section: Introductionmentioning
confidence: 99%